Some Refinements for Numerical Radius Inequalities of Operators (European Journal of Pure and Applied Mathematics, 2025)
Several recent papers gave numerical radius inequalities for sums and products of operators which are defined on a complex separable Hilbert space H. In this paper, we prove a numerical radius inequality which generalizes and refines a recent inequality proved by Kittaneh.
Keywords: Inequality; numerical radius; Operator; Norm